2021
DOI: 10.1017/s0950268821000042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PD-1 gene polymorphism and its interaction with tea drinking on susceptibility to tuberculosis

Abstract: The aim of this study was to explore the impact of polymorphism of PD-1 gene and its interaction with tea drinking on susceptibility to tuberculosis (TB). A total of 503 patients with TB and 494 controls were enrolled in this case–control study. Three single-nucleotide polymorphisms of PD-1 (rs7568402, rs2227982 and rs36084323) were genotyped and unconditional logistic regression analysis was used to identify the association between PD-1 polymorphism and TB, while marginal structural linear odds models were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous groups have reported that some polymorphisms of PDCD1 , CTLA4 , and HAVCR2 are associated with TB risk [ 25 – 28 ]. In this study, we found a sex-dependent association of TB risk with the AG genotype of PDCD1 rs2227982, TC genotype of HAVCR2 rs13170556, AG genotype of CTLA4 rs231775, and CT genotype of CTLA4 rs231779.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous groups have reported that some polymorphisms of PDCD1 , CTLA4 , and HAVCR2 are associated with TB risk [ 25 – 28 ]. In this study, we found a sex-dependent association of TB risk with the AG genotype of PDCD1 rs2227982, TC genotype of HAVCR2 rs13170556, AG genotype of CTLA4 rs231775, and CT genotype of CTLA4 rs231779.…”
Section: Discussionmentioning
confidence: 99%
“…Associations of TB susceptibility with some single nucleotide polymorphisms (SNPs) of PDCD1 and CTLA4 have been reported [25][26][27]. In PDCD1, rs7568402 is linked to increased TB risk [25], and rs3087243 AA in CTLA4 is negatively associated with severe pathology in pulmonary TB [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation